A new robust optimization approach for integrated multi-echelon, multi-product, multi-period supply chain network design under process uncertainty. Issue 1 (July 2015) - Akbari, Ali; Karimi, Behrooz
Abstract Cost-effective supply chain management through integrating strategic decisions (e.g., network design) along with tactical decisions (e.g., production, distribution, and inventory decisions) under various markets, logistics, and production uncertainties is a critical issue for companies in different industries. In this paper, robust design and planning of a multi-echelon, multi-product, multi-period supply chain network considering process uncertainty is addressed. At first, a new robust optimization approach is developed which is capable to take into account two possibly disjoint uncertainty sets for each uncertain parameter. Then this framework is applied to the supply network design problem and the associated robust counterpart is derived. A simulation-based procedure is also proposed to determine appropriate uncertainty budgets. Finally, the applicability of the presented approach is tested through an illustrative example.